2017
DOI: 10.1186/s13071-017-2353-8
|View full text |Cite
|
Sign up to set email alerts
|

The N- and C-terminal carbohydrate recognition domains of Haemonchus contortus galectin bind to distinct receptors of goat PBMC and contribute differently to its immunomodulatory functions in host-parasite interactions

Abstract: Background: Hco-gal-m is a tandem-repeat galectin isolated from the adult worm of Haemonchus contortus. A growing body of studies have demonstrated that Hco-gal-m could exert its immunomodulatory effects on host peripheral blood mononuclear cells (PBMC) to facilitate the immune evasion. Our previous work revealed that C-terminal and N-terminal carbohydrate recognition domains (CRD) of Hco-gal-m had different sugar binding abilities. However, whether different domains of Hco-gal-m account differently for its mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 50 publications
0
22
0
Order By: Relevance
“…The control groups were treated with PBS or recombinant pET32a protein with ConA. The samples were poured in 96-well plate and were cultured at 37 • C and 5% CO 2 for 72 h. Cell proliferation assay was performed by the addition of 10 µL of CCK-8 solution (Beyotime Institute of Biotechnology, Haimen, China) to each well, 4 h before harvesting, and the absorbance values were measured at 450 nm (OD 450 ) using a microplate spectrophotometer (BioRad Laboratories, Hercules, CA, USA) [58]. Cells in the PBS group served as the control and the OD 450 was set as 100%.…”
Section: Cell Proliferation Assaymentioning
confidence: 99%
“…The control groups were treated with PBS or recombinant pET32a protein with ConA. The samples were poured in 96-well plate and were cultured at 37 • C and 5% CO 2 for 72 h. Cell proliferation assay was performed by the addition of 10 µL of CCK-8 solution (Beyotime Institute of Biotechnology, Haimen, China) to each well, 4 h before harvesting, and the absorbance values were measured at 450 nm (OD 450 ) using a microplate spectrophotometer (BioRad Laboratories, Hercules, CA, USA) [58]. Cells in the PBS group served as the control and the OD 450 was set as 100%.…”
Section: Cell Proliferation Assaymentioning
confidence: 99%
“…Recombinant plasmid expression HcADRM (pET-28a (+)/HcADRM; Uniprot: W6NKS2) was provided by Ministry of Education (MOE) joint international Research Laboratory of Animal Health and Food Safety, College of Veterinary Medicine, Nanjing Agriculture University (Nanjing, Jiangsu, China). Escherichia coli BL21 (Vazyme Biotech, Nanjing, Jiangsu, China) transformed with pET-28a (+)/HcADRM was induced, and the recombinant protein was purified as previously described [33]. Briefly, the recombinants were incubated at 37 • C until the optical density at 600 nm (OD 600 ) of the culture reached 0.6.…”
Section: Expression and Purification Of Rhcadrmmentioning
confidence: 99%
“…Immunocytochemistry assays were performed to verify the interaction of HcESPs with goat T cells as previously described [11]. Briefly, freshly sorted T cells (1 × 10 6 cells/mL) were incubated with 20 µg/mL HcESPs at 37 °C for 6 h. After five washes, the cells were fixed with 4% paraformaldehyde for 20 min at room temperature, permeabilized by 0.5% Triton X-100 in PBS for 5 min and blocked with 4% BSA in PBS for 30 min to minimize background staining.…”
Section: Immunofluorescence Assaymentioning
confidence: 99%
“…Due to anthelmintic resistance and the increasing demands for drug-free animal production [10], a better understanding of the mechanisms by which adult worms regulate host immune responses to promote coexistence with hosts may contribute to the exploitation of novel control strategies against H. contortus infection. Importantly, accumulating evidence has revealed that an array of adult H. contortus ES proteins (HcESPs), for example, Hco-gal-m/f [11], HcSTP-1 [12], Miro-1 [13], and Hc-AK [14], contribute to the facilitation of immune evasion by suppressing the proliferation of host peripheral blood mononuclear cells (PBMCs) and the production of protective cytokines.…”
Section: Introductionmentioning
confidence: 99%